Knowledge as a main strategic resource of a company - Шевчук, Олена Анатоліївна (Technology audit and production reserves, 2013)
For a deep comprehension of principles of development of a modern company, the article suggests to consider knowledge as a key strategic resource, providing competitive advantages. It was emphasized that the dominant feature of the modern economy is a monopoly of knowledge. It was noted that recent decades are characterized by wide spreading of information and communication technologies, which contribute to the rate of production and dissemination of knowledge. It was noted that the increase in company profits largely depends on the modernization, technical and technological re-equipment, and the introduction of effective innovations. It was stressed that the exchange value of economic benefits depends on the content of knowledge, information and intelligence. As a result, we have offered the version of the well-known formula for transformation of the advanced value into the capital.